The Implication Of General Allocation Fund, Special Allocation Fund, Profit Sharing Fund To Inequality The Gross Regional Domestic Product In South Sulawesi Province Period 2006-2014 - Muhammad Azizi (IAIN Manado, 2018)
Abstract Research aimed to: (1) the effect of components DAK (Special Allocation Fund) to the reduction of inequality Gross Regional Domestic Product (GRDP) Inter-district in South Sulawesi Province Period 2005-2014; (2) the effect of components DAU (General Allocation Fund) to the reduction of inequality Gross Regional Domestic Product (GRDP) Inter-district in South Sulawesi Province Period 2005-2014; (3) the effect of components DBH (DBH) to the reduction of inequality Gross Regional Domestic Product (GRDP) Inter-district in South Sulawesi Province Period 2005-2014.This study uses secondary data sourced from Statistics South Sulawesi province, data obtained is the result of the final report of the Central Statistics Agency in the form of the GDP of South Sulawesi province, DAU, DAK, DBH and southern Sulawesi province in 2005-2014. Data disnalisis by using SPSS and Williamson Index.The results of this study indicate the results of multiple linear regression above shows that the variable of general allocation funds positive and significant impact on inequality regional South Sulawesi in 2005 s / d 2014, variable special allocation fund a significant negative effect on inequality regional South Sulawesi in 2005 s / d in 2014 and a variable revenue-sharing significant negative effect on regional inequality South Sulawesi in 2005 s / d in 2014;This shows that shows that the magnitude of regional imbalances in South Sulawesi Province happened yet categorized inequality are low because williamson index values <0.03. Keywords: General Allocation Fund, Special Allocation Fund, DBH and Regional Inequality